2018
DOI: 10.1159/000487889
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Weight Stigma in Future Experimental Designs on Physical Activity - Development and Pilot Validation of a Video Instrument

Abstract: Objective: There is a need for more experimental research on weight stigma and physical activity, specifically among men with obesity. Yet, validated procedures are required. The goal of this study was i) to develop a 10-min video instrument for the experimental induction of physical activity-related weight stigma (including a neutral control video), and ii) to collect information with regards to its content, face, construct, and criterion validity. Methods: To ensure content and face validity, two experts gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We have therefore not experienced weight stigmatisation ourselves. However, the team has a research history regarding weight stigma and published several studies on the subject [9,14,62]. Consequently, we are familiar with the subject matter [22].…”
Section: Statement On Positionality Of Research Teammentioning
confidence: 99%
“…We have therefore not experienced weight stigmatisation ourselves. However, the team has a research history regarding weight stigma and published several studies on the subject [9,14,62]. Consequently, we are familiar with the subject matter [22].…”
Section: Statement On Positionality Of Research Teammentioning
confidence: 99%
“…This approach is person-centered, focused on specific target groups to identify what is important to them, taking into account not only health needs but also IT skills, socioeconomic context, interoperability, and integration gaps that may influence the adoption of innovative solutions tailored to improve health outcomes. Of note, overweight or obese patients tend to be marginalized and subjected to a real social stigma [ 31 , 73 ], and digital solutions may be useful to overcome psychological factors that prevent obese patients from starting their journey in a lifestyle change [ 74 ]. Indeed, among the twelve personas developed ( Figure 1 ) by Blueprint Partners, five—Rose, Millie, Ben, Antonio, and Matilde developed later ( Figure 2 )—are overweight or obese due to low physical activity, making them at risk for developing diabetes and becoming socially isolated [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Kushner et al ,32 for example, it was shown that “in contrast to empathy and counselling, scaled stereotyping mean scores showed a regression back to baseline over a year”—which, to an even greater degree, supports the need for research to focus on variables that support lasting effects of anti-stereotyping interventions. Regarding future research methods on ‘anti-fat’ attitudes, Carl and colleagues43 suggest the use of a video instrument, which has just been validated within a pilot study.…”
Section: Discussionmentioning
confidence: 99%